Analisis Kejahatan Ekonomi dalam Praktik Pinjaman Online: Dampak terhadap Masyarakat dan Strategi Penanggulangan - Dwi Yulianto (Jurnal Syntax Admiration, 2024)
Technological developments have triggered the emergence of online loan services (Pinjol) that offer easy access to finance. However, illegal practices in this sector, such as fraud, misuse of personal data, and intimidation, pose serious social and economic impacts for society. This study aims to analyze the forms of economic crime in online lending, its impact on society, and effective countermeasure strategies. The descriptive-analytical research method is used with the approach of literature study and empirical data analysis. The results of the study show that the practice of illegal online lending causes financial losses, psychological pressure, and damages trust in the financial system. Weak regulations and low digital literacy in the community exacerbate this situation. Countermeasures include strengthening regulations, law enforcement based on the concepts of Strict Liability, Absolute Liability, and Vicarious Liability, as well as increasing people's financial literacy. In conclusion, a collaborative approach between the government, OJK, law enforcement, and the public is urgently needed to create a safe and responsible online lending ecosystem.